Growth Performance of Starter Phase Crossbred Native Chickens Fed Silage of Banana Peel - Koni, Theresia Nur Indah; Foenay, Tri Anggarini Yuniwaty; Chrysostomus, Hieronymus Yohanes (Universitas Halu Oleo, 2022)
Banana peel is one of the non-conventional feed ingredients, but its utilization is still limited due to high content of crude fiber and tannins. The usage of 10% tapioca and 21 days of fermentation time in silage production was able to reduce crude fiber and tannin levels of kepok banana peel. A four-week dietary treatment was conducted with 160 day old of joper strain, a cross-bred native chickens, to determine the utilization silage of banana peel (SBP). The birds were randomly assigned to four dietary treatments with five replication of eight chicks each in a completely randomized design. The treatments consisted of banana peel silage inclusion at 0, 10, 20, and 30% in the diet. Data were analyze by analysis of variance (ANOVA) and means were compared using Duncan’s Multiple Range Test. The results showed that inclusion of SBP had significant effect (p<0.05) on weight gain and feed conversion, but had no significant effect (p>0.05) on feed intake. It was concluded that the optimal growth response of broilers was indicated in the inclusion of SBP up to 10% of the diet.Keywords: feed conversion, feed intake, silage banana peel, silage weight gain